Analisis Pemahaman Konsep Siswa Kelas VIII di MTs Al Irsyad Wonosari Pada Materi Fotosintesis - Linda Budi Safitri; Desi Nuzul Agnafia (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to analyze the understanding of the concepts of class VIII students at MTs Al Irsyad Wonosari on the material of photosynthesis. This study uses a descriptive type of research, namely analyzing by describing. The object of this research is class VIII students at MTs Al Irsyad Wonosari, totaling 39 students in the 2021/2022 academic year. The data collection technique uses essay test questions that contain indicators of concept understanding according to Anderson (2001). The results of the analysis of understanding the concept of class VIII A students obtained the results of understanding the concept of explaining the indicators of 60.7%, exemplifying 65.3%, interpreting 41.3%, classifying 38.7%, comparing 93.3%, summarizing 86.7% , 58% inference indicator and an average concept understanding indicator of 63.4% which is included in the good category. Class VIII B obtained the results of class VIII A the results of understanding the concept of explaining indicators were 48.8%, exemplifying 49.6%, interpreting 20.4%, classifying 17.1%, comparing 75%, summarizing 50%, inference indicators 51 .3% and the average concept understanding indicator is 44.6% which is included in the sufficient category. So it can be concluded that the ability to understand the concepts of class VIII students at MTs Al Irsyad Wonosari on photosynthesis material as a whole falls into the sufficient criteria. Most of the students have been able to solve problems that contain indicators of concept understanding.